THE INFLUENCE OF DIGITAL LITERACY AND CREATIVITY ON INTEREST IN DIGITAL ENTREPRENEURSHIP AMONG ECONOMIC EDUCATION STUDENTS OF RIAU UNIVERSITY - Whindy Decha Putri; Suaman Suaman; Fenny Trisnawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of digital literacy and creativity on digital entrepreneurial interest among students of the Economics Education Program at Universitas Riau. The research employed a quantitative approach using a survey method. The population consisted of Economics Education students, with a sample of 102 respondents selected through proportional random sampling. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS version 26. The descriptive analysis results indicate that students’ digital literacy, creativity, and digital entrepreneurial interest are generally at a moderate level. Partial test results show that digital literacy has a positive and significant effect on digital entrepreneurial interest, and creativity also has a positive and significant effect on digital entrepreneurial interest. Simultaneous testing reveals that digital literacy and creativity jointly have a significant effect on students’ digital entrepreneurial interest. The coefficient of determination indicates that digital literacy and creativity explain 60.3% of the variance in digital entrepreneurial interest, while the remaining variance is influenced by other factors outside the research model. This study concludes that strengthening digital literacy and creativity is essential to enhance students’ digital entrepreneurial interest. Therefore, higher education institutions are encouraged to integrate digital literacy and creativity development into entrepreneurship learning to foster digital entrepreneurship among students.